Lab-On-a-Chip an integrated microfluidic device sensitive low-Cost, and Rapid with a syringe pump for Analysis of Ibuprofen - Sakin, Huda; Faris, Rawaa (Iraqi Journal of Laser, 2023)
Abstract: Microfluidic devices present unique advantages for the development of efficient drug assay and screening. The microfluidic platforms might offer a more rapid and cost-effective alternative. Fluids are confined in devices that have a significant dimension on the micrometer scale. Due to this extreme confinement, the volumes used for drug assays are tiny (milliliters to femtoliters). In this research, a microfluidic chip consists of micro-channels carved on substrate materials built by using Acrylic (Polymethyl Methacrylate, PMMA) chip was designed using a Carbon Dioxide (CO2) laser machine. The CO2 parameters have influence on the width, depth, roughness of the chip. In order to have regular channel surface, and low roughness the laser power (60 W), with scanning speed (250 m/s) for allows us to obtain microchannels with a minimum diameter of width (450 µm), depth of the channels was 89.4 µm and( Arithmetic Average Roughness Ra = 2.3), (Relative roughness, Ɛ = 5%) surface roughness with high accuracy and good surface quality. The functionalized multiwalled carbon nanotubes (F-MWCNTs) was used to enhance the drug signal inorder to detect very tiny Ibuprofen concentration. In this work, laser microfluidic sensor have high accuracy in Ibuprofen detection compared to the traditional method(UV-VIS) spectrophotometer with LOD equal to 0.25 nM, 1000µM respectively.